2020
DOI: 10.21106/ijtmrph.182
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Seizure Control Among Patients with Epilepsy at Two Referral Hospitals in Zambia

Abstract: Background: Epilepsy is a neurological condition that has proven to be a major public health challenge worldwide, including Zambia. Despite the availability of many treatment alternatives, people with epilepsy still experience seizures. There is paucity of information on the control of seizures and associated factors in Zambia. Methods: A cross sectional study was conducted among epileptic patients at Kitwe and Ndola Teaching Hospitals, two referral hospitals in Northern Zambia, from September 2 to Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our study's-controlled seizure rate of 62.4% was lower than studies carried out in China, Canada, Turkey, Spain, which showed controlled seizure rates of 72%, 68.4%, 67.5%, 81%, respectively, but higher than Scotland, Zambia, Ethiopia-Ambo region, Ethiopia-Mizan Tepi, Ethiopia-Jimma, and Ethiopia-Gondar regions, which showed 59.2%, 23.6%, 55.3%, 39.2%, 54.1%, and 94%, respectively 22,[27][28][29]33,34,39,[51][52][53] (Figure 1).…”
Section: Dovepressmentioning
confidence: 77%
See 1 more Smart Citation
“…Our study's-controlled seizure rate of 62.4% was lower than studies carried out in China, Canada, Turkey, Spain, which showed controlled seizure rates of 72%, 68.4%, 67.5%, 81%, respectively, but higher than Scotland, Zambia, Ethiopia-Ambo region, Ethiopia-Mizan Tepi, Ethiopia-Jimma, and Ethiopia-Gondar regions, which showed 59.2%, 23.6%, 55.3%, 39.2%, 54.1%, and 94%, respectively 22,[27][28][29]33,34,39,[51][52][53] (Figure 1).…”
Section: Dovepressmentioning
confidence: 77%
“…Similarly, epilepsy treatment outcomes in studies conducted in Zambia and two Jimma studies, Mizan Tepi, Ayder, Addis Ababa, and Afar, were affected by the degree of adherence to ASMs. 27 , 28 , 41 , 53 , 67 , 68 Even though the clinician orders the appropriate medication and performs the right dosing titration, it will be challenging to control seizures in patients with epilepsy if they are not taking the medications properly.…”
Section: Discussionmentioning
confidence: 99%
“…It is a referral hospital with a bed capacity of 851 and supports districts in Copperbelt, Luapula and North-Western Provinces of Zambia. Its catchment population is mainly composed of formally employed individuals and attends to referrals of different socio-economic statuses from the provinces it covers [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%